Modeling of a SOFC-HT battery hybrid system for optimal design of off-grid base transceiver station. (16th November 2017) - Brunaccini, G.; Sergi, F.; Aloisio, D.; Ferraro, M.; Blesznowski, M.; Kupecki, J.; Motylinski, K.; Antonucci, V.
Abstract: This work aims at the development of a simulation tool to optimize the design of a hybrid fuel cell/battery system to supply ICT equipment. In the framework of the ONSITE European project, which deals with a hybrid (fuel cell and batteries) RBS (Radio Base Stations) supply system, a modeling activity is carried out to optimize the system operations. The developed algorithms separately implement a Solid Oxide Fuel Cell system and a high temperature Sodium Nickel Chloride battery for design purpose and collect them in a unique model for devices interaction (i.e. power production, storage, and control). Moreover, a Computational Fluid Dynamics battery model is developed to analyse the heat transfer while the SOFC stack generates excessive heat during operation and outlet hot gases can be effectively used. Since the SNC batteries need heat during charging process (to maintain their operating temperature) and, conversely, the reactions are exothermic in discharge mode, the described approach aims at combining SNC batteries with micro-CHP unit to optimize the energy flows. The implementation requires several alternative designs and variant analysis to secure proper operation of battery and power generation unit. The model developed and shown in this paper is a dedicated tool for the simulation of the hybrid system proposed and for the optimal designing of each main sub component. Highlights: A tool was developed to design SOFC-SNC battery prototype to supply ICT systems. The hybridization allowed to tailor the supply system around the expected load. The battery model consists of two virtual batteries managed by a logic network. The thermal integration was studied to improve the energy conversion efficiency.